Analisis Luas Lahan Kelapa Sawit Menggunakan Metode FuzzyAHP Terhadap Resiko Pelaku Usaha - Paduloh; Rakhmat Purnomo; Murwan Widyantoro (Jurnal Jaring SainTek, 2019)
The aim of this study was to identify the risk of oil palm land ownership and the relationship between oil palm land area and farmers' income, the level of welfare of farmers and workers in oil palm plantations. This research can be a reference for businesses who will invest in oil palm plantations. The research was conducted by giving questionnaires to experts, the experts in question were oil palm industry players and were able to make decisions. The results of the questionnaire are processed using Fuzzy AHP to determine the degree of importance of each expert. The results obtained are the biggest risk at the actor level is the farmer, at the level of the highest risk criteria is the increase in the amount of supply while at the alternative level is the risk of quality.